(untitled) (Journal of National Institute of Neurosciences Bangladesh, 2022)
Background: As control of hypertension is crucial in patients with acute glomerulonephritis (AGN) to avoid life-threatening complications and deaths. Objectives: This study was done to see the efficacy of captopril and nifedipine to control hypertension in AGN in respect to their clinical response, duration and cost of treatment. Methodology: This randomized clinical trial was done among children ages ranging from 3 to 12 years who were suffering from AGN with hypertension and/or its complications. After enrolment the patients were randomly divided into two groups as Group A and Group B. Both groups received the standard management of AGN. In addition, children in group-A received captopril (dose 0.5 up to 6 mg/kg/day) and children in group B received nifedipine (0.25 up to 0.5 mg/kg/day). Their effectiveness in relation to timing of response, duration of therapy, side effects and cost effectiveness of the drugs were assessed statistically and at p value of <0.05 the result was considered significant. Results: Mean systolic and diastolic blood pressure (BP) in group A were 134.8±9.31 and 94.97±6.33 mm Hg respectively and those in group B were 131.96±8.16 and 92.80±9.11 mm Hg respectively. After intervention both the drugs were found effective to normalize BP (BP <90th centile). The mean time/duration taken to normalize BP by captopril was 4.86 ± 1.73 days and that by nifedipine was 2.17 ±1.73 days respectively and this difference is significant (p<0.01). The mean total duration of treatment required for captopril was 6.75 ± 2.04 days and that for nifedepine was 3.67 ± 1.24 days and this is highly significant (p<0.001). The average cost of captopril treatment was 11.95 ± 8.65 taka and that of nifedipine was 1.77±1.15 taka respectively and it is highly significant (p<0.001). The mean duration of hospital stay in captopril group was 8.59 ± 2.64 days and that in nifedipine group was 5.53 ± 1.49 days and it was very significant (p<0.005). Conclusion: Nifedipine is more effective to control BP in relation to its earlier clinical response, duration and cost of treatment than Captopril in children with AGN. Journal of National Institute of Neurosciences Bangladesh, January 2022; 8(1):28-32